An interactive review on the role of Tocotrienols in the neurodegenerative disorders - Naomi, Ruth; Shafie, Nurul Husna; Kaniappan, Priyatharisni; Bahari, Hasnah (Frontiers Media, 2021)
Neurodegenerative disorders, such as Parkinson's and Alzheimer's disease, are claimed to be of major concern causing a significant disease burden worldwide. Oxidative stress, mitochondrial dysfunction and nerve damage are the main reasons for the emergence of these diseases. The formation of reactive oxygen species (ROS) is the common chemical molecule that is formed from all these three interdependent mechanisms which is highly reactive toward the neuronal cells. For these reasons, the administration of tocotrienols (T3s), which is a potent antioxidant, is proven to cater to this problem, through in vitro and in vivo investigations. Interestingly, their therapeutic potentials are not only limited to antioxidant property but also to being able to reverse the neuronal damage and act as a shield for mitochondria dysfunction. Thereby, T3s prevents the damage to the neurons. In regards to this statement, in this review, we focused on summarizing and discussing the potential therapeutic role of T3s on Alzheimer's and Parkinson's diseases, and their protective mechanisms based on evidence from the in vitro and in vivo studies. However, there is no clinical trial conducted to prove the efficacy of T3s for Alzheimer's and Parkinson's subjects. As such, the therapeutic role of T3s for these neurodegenerative disorders is still under debate.